A study on the potential of carbon-based nanomaterials for enhancement of evaporation and water production. (2nd November 2019) - Ghafurian, Mohammad Mustafa; Niazmand, Hamid; Dastjerd, Fateme Tavakoli; Mahian, Omid
Graphical abstract: Highlights: Effect of nanofluids in solar steam and pure water generation was investigated. The performance of MWCNT, SWCNT, GO and GNP nanomaterials was compared. The sensible heat storage of nanofluids during the light on and off were studied. High quality of distilled water was proved by seawater desalination using nanofluids. Abstract: In the present study, the performance of water based-nanofluids containing four different types of carbon nanostructures for solar vapor generation has experimentally been investigated. The considered nanofluids are multi-walled carbon nanotube, single-walled carbon nanotube, graphene nanoplate and graphene oxide. Nanofluids with three nanoparticle mass concentrations of 0.001%, 0.002%, and 0.004% were prepared and their evaporation characteristics were investigated for solar radiation intensities in the range of 1.5 and 3.5 Suns. The results indicated that the multi-walled carbon nanotube nanofluid with a mass concentration of 0.004% provides the highest evaporation rate with the maximum total efficiency of 94% at 3.5 Suns. The total efficiencies for nanofluids containing the single-walled carbon nanotube, graphene nanoplate and graphene oxide at similar conditions and that of pure water, respectively, are about 91%, 90%, 81% and, 54%. Furthermore, it is observed that for the mass concentration of 0.004%, the evaporation rate with respect to water increases to about 72%, 63%, 58% and 36%, respectively, for the multi-walled carbon nanotube, the single-walled carbon nanotube, graphene nanoplate and graphene oxide nanofluids. As far as the sensible heat is concerned, graphene oxide shows the most considerable sensible heating efficiency at the mass concentration of 0.004% with the maximum fluid bulk temperature rise of 20.5 °C, which is 40% higher than that of water. Finally, it was found that increasing the radiation intensity from 1.5 to 3.5 Suns improves the evaporation rate; however, the sensible heat efficiency is more influenced such that the evaporation efficiency declines. The quality of the produced water from a seawater sample is also examined and it was shown that it is well below the limitations of the drinking water standards.